Preliminary study on unlocking growth and yield potential of USDA foxtail millet (Setaria italica L.) lines with NPK fertilization - Hira Shahzadi; Shahbaz Khan; Abdulrahman Al-Hashimi; Shahzad M. A. Basra; Kashf Mehmood; Muhammad Ashfaq Wahid; Muhammad Nawaz; Sohail Irshad; Abdul Haseeb; Afroz Rais; Safia Gul; Danish Ibrar; et al. (BMC Plant Biology)
Abstract Foxtail millet (Setaria italica L.) is nutritionally superior to other cereals of the family Poaceae, with the potential to perform better in marginal environments. In the present context of climate change, ecologically sound and low-input foxtail millet varieties can be chosen for agricultural sustainability. The planned research was carried out at the green house of the Department of Agronomy, University of Agriculture, Faisalabad, Pakistan, to investigate the impact of various levels of NPK fertilizer on the growth, development, and yield of foxtail millet lines from USDA germplasm. Eight lines of foxtail millet; U2, V19, V73, V93, V101, V106, V107, and V111, were under study along with NPK fertilizers’ treatments; T1 = 000 NPK as a control, T2 = 20:15:15 NPK, T3 = 30:20:20 NPK, T4 = 40:25:25 NPK, and T5 = 50:30:30 NPK (kg ha− 1). NPK treatments were applied twice during the study periods: first dose was applied after one week of the emergence of seedlings and the second dose was applied at the age of four weeks of seedlings. The time to 50% emergence ranged from 4.33 (V111) to 5.92 (U2) days, and the emergence was highest in V111 (10.02), and V19 had the lowest emergence index of 4.95. Furthermore, all genotypes achieved a complete final emergence percentage of 100, except U2 (92.89%) and V19 (89.33%). The highest growth rate and assimilation rate were observed in V111 and V107 under the impact of treatment 5. Among the different treatments, T3 resulted in the maximum plant height, panicle length, and grain yield per panicle. The highest panicle weight and grain yield per panicle were observed in line V106. Line V107 synthesized the highest chlorophyll a while V93 produced highest chlorophyll b contents which is statistically similar toV19. Line V19 had the highest total chlorophyll and V93 produced the highest carotenoid contents. Application of NPK at the rate of 50:30:30 kg ha− 1 produced maximum chlorophyll a (23%), b (15.8%), total chlorophyll contents (14.2%), plant fresh biomass (2.06%), and grain yield (23.6%) as compared to control treatment. Overall, T3 (30:20:20) and T5 (50:30:30) were observed to be better as compared to other treatments. With respect to growth, yield, and chlorophyll contents, lines U2, V19, V93, V106, V107, and V111 were observed to be potentially superior.